Recovery ion Hg2+ dari limbah cair industri penambangan emas rakyat dengan metode presipitasi sulfida dan hidroksida - Ilma Fadlilah; Agus Prasetya; Panut Mulyono (Jurnal Rekayasa Proses, 2018)
Unlicensed gold mining activities using mercury (Hg) as a gold element binder is called the amalgamation process. Mercury is a heavy metal and categorized as toxic material. The use of mercury can potentially cause a pollution in environment, especially the aquatic system. For overcoming the heavy metals of mercury in liquid waste, it needs an alternative wastewater treatment method e.g. chemical precipitation. This study is aimed to recover Hg2+ ions from liquid wastes by using sulphide precipitation and hydroxide methods. This research studied the effect of pH on Hg2+ ions which is deposited in the precipitation process and evaluated the rate of Hg2+ precipitation formation. Precipitation was carried out by using sodium sulphide (Na2S) 0.3 M and Ca(OH)2 0.004 M as a precipitation agent with a rapid mixing speed for about 200 rpm for 3 minutes and continued with slow mixing for about 40 rpm for 30 minutes. Then, the liquid sample was left for 24 hours to precipitate. The results showed that precipitation method by using Na2S solution can decrease the content of Hg in HgCl2 synthetic waste. Optimum mass of HgS precipitate of 0.046 g was achieved at pH 9 with a removal efficiency percentage up to 99.81%. The rate of formation of HgS precipitate is 0.4mg/ hour. While, hydroxide precipitation method can decrease mercury level up to 90.11% at pH 12 and mass of Hg (OH)2 precipitate obtained is 0.28 g. However, the result of EDX analysis of the precipitate of Hg (OH)2 showed that the content of Hg precipitate is still low at 0.28 wt.%.